Effect of dose reduction of supplemental zinc for childhood diarrhoea: study protocol for a double-masked, randomised controlled trial in India and Tanzania. Issue 1 (24th April 2019) - Somji, Sarah S; Dhingra, Pratibha; Dhingra, Usha; Dutta, Arup; Devi, Prabhabati; Kumar, Jitendra; Deb, Saikat; Semwal, Om Prakash; Sazawal, Sunil; Manji, Karim; Kisenge, Rodrick; Bakari, Mohamed; et al.
Abstract : Background: Diarrhoea-associated mortality and morbidity are highest in infants and young children in low-income and middle-income countries (LMICs). Zinc supplementation during acute diarrhoea has been shown to reduce the duration of illness and the risk of persistent diarrhoea. However, vomiting with zinc supplementation is a common side effect that may interfere with compliance and programmatic scale-up, and may be related to the dose prescribed. Methods/design: The Zinc Therapeutic Dose Trial (ZTDT) is a two-centre (Tanzania and India), three-arm randomised, double-blind controlled non-inferiority trial. Children 6–59 months of age with acute diarrhoea are eligible to participate. Enrolled children (1500 per arm; 4500 total) will be randomly allocated to receive 5, 10 or 20 mg of zinc sulfate daily for 14 days and will be followed up for 60 days after enrolment. All children will receive WHO/Unicef Integrated Management of Childhood Illness standard of care (oral or intravenous rehydration and zinc as indicated and feeding advice). The primary efficacy outcomes of the trial are the percentage of subjects with diarrhoea duration >5 days, the mean total number of loose or watery stools after enrolment and the proportion of children vomiting within 30 min of zinc administration. Discussion: The ZTDT trial will determine the optimal dose of therapeutic zinc supplements for treatment of acute diarrhoea in children aged 6–59 months in two LMICs. The results of the trial are likely to be generalisable to childhood acute diarrhoea in similar resource-limited settings and may influence global policy about zinc supplementation dosage during acute diarrhoea. Trial registration number: NCT03078842 . Trial status: Enrolment began in January 2017 and follow-up is estimated to be completed by April 2019. As of 1 February 2019, 742 children are still contributing data to the ZTDT study.